SERUM FERRITIN LEVEL IN CHILDREN WITH β-THALASSEMIA MAJOR: A HOSPITAL BASED PILOT STUDY - GUPTA, DIVYA; DIXIT, JAGDAMBA (International Journal of Current Pharmaceutical Research, 2026)
Objective: To study the serum ferritin level in children with β-TM patients. Methods: Clinico-pathological details of β-TM patient’s were entered into a Microsoft Excel and exported to SPSS version 21 (IBM SPSS® software, Chicago, US). P value<0.05 was considered as statistically significant. Results: Significant correlation between serum ferritin value (P-value 0.001) (mean 1868.67and SD value 1427.68) and number of blood transfusion (mean 67.77 and SD value 66.88) have been observed. Increased number of blood transfusion is associated with increased serum ferritin value (P-value 0.001 and correlation coefficient 0.536**) which represent the iron overload. Conclusion: Regular monitoring of serum ferritin, and other biochemical parameters will improve the health of β-TM patients. Higher numbers of study samples are needed to validate the result of β-TM patients. Significant correlation has been observed in serum ferritin which shows the iron overload in β-TM patients. Furthermore we need to study on larger sample size for iron overload in β-TM patients.